(untitled) (Bangladesh Journal of Agricultural Research, 2026)
The experiment was conducted at the farmers’ fields of Kalkini and sadar upazila of Madaripur, during two consecutive years 2019-20 and 2020-21 to evaluate the performance of yield, productivity and proﬁtability of Mustard-Mungbean-T. aman cropping pattern through incorporating, short duration and high yielding crop varieties with integrated nutrient management. The experiment was laid out in a randomized complete block design with three dispersed replications. The cropping cycle was with three crops, nine varieties namely Mustard: var. BARI Sarisha-14, BARI Sarisha-17, BARI Sarisha-11; Mungbean: var. BARI Mungbean-6, BARI Mungbean-8, BINA Mungbean-8; T. aman: var. BRRI dhan 57, BRRI dhan 71 and BRRI dhan 75 and three fertilizer levels (F1 = Recommended Fertilizer Dose, RFD from inorganic source as per soil test bases, STB; F2 = RFD on STB + 5 t ha-1 cowdung, integrated plant nutrient system, IPNS approach; F3 = Farmers practices). Highest yield as well as by-product yield, rice equivalent yield ( REY) (16.12 t ha-1 yr-1), gross return (3,86,880 Tk ha-1 yr-1), total variable cost (1,36,621 Tk ha-1 yr-1), gross margin (2,50,259 Tk ha-1 yr-1) and marginal benefit cost ratio (2.83) were obtained from the treatment combination of mustard var. BARI Sarisha-14, mungbean var. BARI Mung-6 and rice var. BRRI dhan71 with integrated plant nutrient system (IPNS) and the lowest from farmers’ practices. IPNS based fertilizer management in this cropping pattern performed better compared to other fertilizer management practices. Higher REY indicates that improved cropping pattern Mustard (var. BARI Sarisha-14/BARI Sarisha-17)-Mungbean (var. BARI Mung-6)-T. aman (var. BRRI dhan57/BRRI dhan71/BRRI dhan75) could be suitable in Madaripur for increasing crop productivity cropping intensity as well as profitability. Bangladesh J. Agril. Res. 47(4): 383-399, December 2022